In Vitro Study Of The Effect Of Corn Silk On Glucose Uptake By Isolated Rat Hemi-Diaphragm - Nour, A. H.; M., Ghada; Eltohami, M. S.; Mudawi, Mahmoud M. E. (WJPR, Medical University, Bulgaria, 2014)
In the present study the methanolic extract of corn silk was evaluated for antidiabetic activity. The antidiabetic activity was studied using the glucose uptake by isolated rat hemi-diaphragm using in-vitro model. Corn silk increased the uptake of glucose by isolated rat hemidiaphragm significantly (P<0.001) and was found to be more effective than insulin. It appears that corn silk has direct peripheral action on glucose uptake. The value of glucose uptake by rat hemi-diaphragm after addition of corn silk extract was 109±1 as compared to control (12± 1) and Insulin (49 ± 8)mg/g/30min .These results strongly suggest that Corn silk will be alternative choice for the treatment of diabetes mellitus.